Penerapan Metode ARAS Dalam Pemilihan Objek Wisata yang Terbaik - Thamriansyah; Muhammad Al Farid; Jesdyka Calvin Samuel Purba; Safira Izzati; Rizki Alfadilah Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Abstract?Tourism is an important sector in the economy of Central Tapanuli Regency, with various tourist attractions that have great potential to be developed as leading destinations. The existence of diverse tourist attractions, ranging from beaches, tropical forests, waterfalls, to lakes, makes this region rich in natural potential that can attract local and foreign tourists. This study aims to determine the best tourist attractions in the Tapanuli Tengah Regency area using the ARAS (Additive Ratio Assessment) method. This method is used because it is able to assess various alternatives objectively based on certain criteria, such as Natural Attraction, Ease of Access, Supporting Facilities, Environmental Sustainability, and Economic Impact on the local community. The assessment process was carried out by calculating the normalization and integration values of each criterion, which were then used to determine the final ranking of each tourist attraction. The ARAS method was used to calculate the normalization and integrated values of each predetermined criterion, thereby providing an objective ranking for each tourist attraction. The analysis results show that Pandan Beach ranks first with the highest optimal value of 1, followed by Sibolga Tropical Forest (0.9659), Sibolangit Waterfall (0.9175), and Linting Lake (0.9114). Meanwhile, Samosir Island ranks last with a score of 0.8558, indicating the need for improvement in several aspects